The Theatre and Its Magic in Language Teaching & Learning - Zainal Abdul Latif (International Conference on Languages and Arts, 2012)
So far little has been done to exploit the obvious advantages of theatre as an instrument of language teaching and learning in schools. Part of the reason why theatre has received little attention in our education system is perhaps the confusion regarding the term ‘theatre’ itself. To parents, ‘doing theatre’ is playing, and playing is bad for learning. Children should stop playing and start learning, once they start schooling. To many teachers and headmasters, theatre is nothing more than the annual presentation of the School Play in conjunction with Speech Day or Canteen Day. This often results in poorly performed plays which are embarrassing, for the audience as well as the actors. And certainly, except for the few chosen to act, the majority of the children do not gain much linguistic skills. Thus theatre is shunned away and teachers are apprehensive about using theatre as a teaching method. This paper will therefore try to show the potentials and the magic of theatre in the teaching and learning of language. What we need to do, is to re-define what is meant by the word ‘theatre’, and how it can be used creatively for our learning purposes. Hopefully, after this delivery, teachers are not only motivated to tryand use theatre, but also know how to use it effectively.